KHẢ NĂNG ỨNG DỤNG THIẾT BỊ RITM-MET VÀ EGOSCOP ĐỂ ĐÁNH GIÁ ĐẶC ĐIỂM TÂM SINH LÝ CỦA BỘ ĐỘ - Bùi, Thị Hương; Trần, Thị Nhài; Nguyễn, Hồng Quang (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE POSSIBILITY OF USING SYSTEMS RITM-MET AND EGOSCOP FOR ASSESSING PSYCHOPHYSIOLOGICAL CHARACTERISTICS OF SOLDIERS Two automatic program-apparatus complexes including Ritm-MET and Egoscop were used to assess the psychophysiological and cognitive characteristics of different worker groups of in various professional activities, including a group of soldiers working under extra-hard and dangerous conditions. The results of the study indicated that these complexes provide opportunities for safely, quickly, simply, effectively, objectively evaluating psychophysiological characteristics. The obtained data have a high level of information and predictability. The two devices can be supported to traditional health assessment methods.